Bioaugmented composting of Jatropha de‐oiled cake and vegetable waste under aerobic and partial anaerobic conditions. (26th June 2012) - Chaturvedi, Shivani; Kumar, Ashwani; Singh, Balraj; Nain, Lata; Joshi, Monica; Satya, Santosh
Abstract This study was conducted to assess the effect of microbial inoculation in Jatropha cake composting with different vegetable waste. The microbial inoculums composed of fungal strains (Aspergillus awamori, Aspergillus nidulans, Trichoderma viride, Phanerochaete chrysosporium) and bacterial inoculums (Pseudomonas striata as phosphorus solublizer and Azotobacter chroococcum as nitrogen fixer) were added to the compost mixture after the thermophilic phase was over for bioaugmenting of Jatropha cake under aerobic and partial anaerobic conditions. Addition of both fungal and bacterial inoculum with mixed substrate (Jatropha cake + vegetable waste) during composting (aerobic and partial anaerobic) showed, better results as compared to compost with only fungal inoculants. Increased enzymatic activity initially, during composting (like dehydrogenase, alkaline phosphatase activity and FDA) proved role of inoculated microbes in rapid decomposition. Analysis of compost (with both bacterial and fungal inoculum) showed presence of high humus (12.7%), humic acid (0.5%), fulvic acid (5.68%), soluble protein content and low C/N ratio. Decreased in concentration of extractable metals (Cu, Fe and Mn) were recorded at maturity in all the substrate composts. The C/N ratio was significantly correlated to parameters like humic acid, humus, fulvic acid, protein and also microbial activity parameters. We conclude that the composting of de‐oiled Jatropha cake with different vegetables waste could be feasible and sustainable approach in recycling of agricultural and industrial residues in huge quantities.